2021
DOI: 10.3390/jcm10163591
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Deep Learning Models for Cervical Vertebral Maturation Stage Classification on Lateral Cephalometric Radiographs

Abstract: The purpose of this study is to evaluate and compare the performance of six state-of-the-art convolutional neural network (CNN)-based deep learning models for cervical vertebral maturation (CVM) on lateral cephalometric radiographs, and implement visualization of CVM classification for each model using gradient-weighted class activation map (Grad-CAM) technology. A total of 600 lateral cephalometric radiographs obtained from patients aged 6–19 years between 2013 and 2020 in Pusan National University Dental Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 35 publications
0
38
1
1
Order By: Relevance
“…These are opposite to feature learning, which is the basic principle of deep learning. Seo et al presented a benchmarking result using six deep learning models that are variants of ResNet, GoogLenet, and MobileNet [17]. Their system is semi-automatic since it requires manual cropping of ROI as preprocessing.…”
Section: Of 12mentioning
confidence: 99%
“…These are opposite to feature learning, which is the basic principle of deep learning. Seo et al presented a benchmarking result using six deep learning models that are variants of ResNet, GoogLenet, and MobileNet [17]. Their system is semi-automatic since it requires manual cropping of ROI as preprocessing.…”
Section: Of 12mentioning
confidence: 99%
“…Many scholars have tried to use CNNs for image auxiliary diagnosis in the field of orthodontics. Seo used CNNs to classify the cervical vertebral maturation stages on 600 lateral cephalometric radiographs [ 6 ]. Yoon used cascaded CNNs for landmark detection in cephalometric analyses with a database of 600 samples [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…They stated that most studied DL techniques classify CVM by focusing on a specific area (region of interest) of the cervical vertebrae. Thus, they suggested that application of high-quality input data and better-performing CNN architectures that are capable of segmenting images will help in creating models with higher performance [29].…”
Section: Discussionmentioning
confidence: 99%